iPod fully loaded : - Ihnatko, Andy (Wiley, 2007)
Let Mac guru Andy Ihnatko show you how to put everything but the kitchen sink on your iPod—from old LPs, radio programs, television shows, and movies to spreadsheets, presentations, and PC rescue files. You'll quickly discover that music is only a small part of the picture as you learn how to record TV shows for an iPod, record radio broadcasts and automatically convert them into podcasts, convert Web pages into formats that can be read or listened to on an iPod, and even translate Microsoft Word, Excel, or PowerPoint documents for the iPod screen. Whether you're a PC or a Mac user, or have a past, present, or even future iPod, Inhantko advice works perfectly